Tinjauan Yuridis Relevansi Pemenuhan Standar Pelayanan Kesehatan dalam Penguatan Pelayanan Kesehatan Primer - Kurniawan, Erwin; Fakih, M; Zazili, Ahmad; Rodliyah, Nunung; Efendia, Malicia (Universitas Sang Bumi Ruwa Jurai, 2025)
The right to health, as a fundamental part of human rights, demands the commitment of the state to provide quality and equitable health services. Puskesmas, as the frontline, play a crucial role in accessibility and health system strengthening. However, the reality on the ground shows that there are challenges, such as damage to facilities and incomplete laboratories at several Puskesmas in Central Lampung District, including Puskesmas Wates. This problem raises a critical question: How is the relevance of fulfilling health service standards to the realization of strengthening primary health services at Puskesmas Wates Lampung Central. This research uses normative legal methods, with a statutory and analytical approach, examining primary, secondary, and tertiary legal materials. The focus is on reviewing the Decree of the Minister of Health Number HK.01.07/Menkes/1047/2024 on Equipment Standards. The results of the study are expected to identify the significance of the fulfillment of equipment standards in improving the quality of service and capacity of Puskesmas Wates, and provide policy recommendations for optimizing the strengthening of primary health services in the context of fulfilling the right to public health